2020
DOI: 10.12997/jla.2020.9.3.435
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Role of Dyslipidemia in COVID-19 Severity: an Umbrella Review of Systematic Reviews

Abstract: Objective: The aim of this study was to analyze the available knowledge about the potential association between dyslipidemia and the severity of coronavirus disease 2019 (COVID-19) as reported in previous published systematic reviews. Methods: In this umbrella review (an overview of systematic reviews), we investigated the association between dyslipidemia and COVID-19 severity. A systematic search was performed of 4 main electronic databases (MEDLINE, Embase, Scopus, and the Cochrane Library databases) from in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
0
8

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 67 publications
4
59
0
8
Order By: Relevance
“…A causal link between cardiovascular disease and COVID-19 outcomes, including thrombotic complications, has been proposed previously (23)(24)(25) but how exactly such clinical events relate to platelet activation phenotypes is not clear. Thus, we first assessed CD62P expression, both basal and following TRAP stimulation, in hospitalized COVID-19 patients that exhibited clinically evident thrombosis.…”
Section: Resultsmentioning
confidence: 97%
“…A causal link between cardiovascular disease and COVID-19 outcomes, including thrombotic complications, has been proposed previously (23)(24)(25) but how exactly such clinical events relate to platelet activation phenotypes is not clear. Thus, we first assessed CD62P expression, both basal and following TRAP stimulation, in hospitalized COVID-19 patients that exhibited clinically evident thrombosis.…”
Section: Resultsmentioning
confidence: 97%
“…Several studies have described rapid changes in the lipid profile in response to COVID-19 and the progression of the disease 4 . Therefore, a major gap may exist between the presence of dyslipidaemia prior to viral infection and the time at which lipid disturbances were detected at the time of hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…High blood pressure and dysglycaemia are associated with a worse prognosis; however, although dyslipidaemia is one of the main cardiovascular risk factors, the association between baseline lipid levels and the prognosis has been less frequently studied. In this respect, a recent umbrella review of systematic reviews suggested that dyslipidaemia may play a role in the severity of SARS-CoV-2 infection 4 .…”
Section: Introductionmentioning
confidence: 99%
“…This study was performed on patients who have not yet received treatment for Covid-19 disease. Previous studies suggested dyslipidemia in viral infections [12,13] and COVID-19 as well [14,15]. Various studies have been performed on the role of cholesterol in pulmonary function.…”
Section: Discussionmentioning
confidence: 99%